Praktik Jual Beli Tanpa Akad : doi 10.58569/jies.v1i2.583 - Fitriani, Alfiana Novi; Oryza Sativa , Enes; Fajrussalam , Hisny (Journal of Islamic Education Studies, 2023)
Buying and selling is one form of relationship between human beings. There are various procedures, laws and buying and selling rules in Islam that have been regulated. One of the rules of buying and selling in Islam which until now has rarely been practiced in society, namely regarding the process of buying and selling without a sale and purchase contract. This study aims to find out whether or not the practice of buying and selling without a contract is legal. This study uses a literature review method by collecting and reviewing sources related to the discussion in this study. The results of this study can be concluded that the process of buying and selling without a contract is legalized by some scholars, considering that this has become a community habit